Eukaryotic initiation factors: central factor associating mRNA translational plasticity during neuropathic pain progression - Xinshuo Li; Haibo Zhan; Xindan Zhang; Jiayi Li; Xiangrui Li; Xihua Lu; Changhong Miao; Chunli Zhou; Zhen Zhang (Frontiers in Neurology)
Neuropathic pain causes plasticity in the nervous system, which is often associated with altered protein synthesis. Proteins are the key executors of cellular functions, and their alteration is closely related to the occurrence of neuropathic pain. Protein synthesis is a finely regulated process involving the interaction of multiple biomolecules. Among them, the eukaryotic translation initiation factors (eIFs) are a group of key regulatory proteins that control the initiation phase of protein translation and thus influence the rate and type of protein synthesis. Recent studies have shown that the eIFs are involved in the regulation of neuropathic pain regulating translation through phosphorylation and affecting the transmission and processing of neuropathic pain signals. Among them, eIF4E and eIF2α, as core initiation factors, changes in their expression and activity are closely associated with various neuropathic pain. This review aims to summarize the evidence for the involvement of the eIFs, especially eIF4E and eIF2α, in pain-associated mRNA translational plasticity, and to propose relevant therapeutic approaches. We hope that this review will provide important ideas for future research on the mechanisms of neuropathic pain and new targets for the treatment of neuropathic pain.